Influence of entrepreneurial orientation in export performance - Rua, Orlando Lima (2015)
This study aims at investigating the influence that entrepreneurial orientation has on export performance of Portuguese footwear small and mediumenterprises (SMEs). Therefore, a quantitative methodological approach was used, conducting a descriptive, exploratory and transversal empirical study, having applied a questionnaire to a sample of Portuguese companies exporting footwear. The research results suggest that entrepreneurial orientation enhances export performance in the analysed SMEs, particularly innovation and proactiveness, through the amount of funds invested, human resources dedicated to this activity, number of new products or services introduced in the market and frequent change in product lines or services and materialization of a long-term perspective, which is accompanied by innovative activities or new businesses. Therefore, the findings sustain the necessity to invest in entrepreneurial orientation as a strategic determinant, which contributes to the growth of small firms in foreignmarkets. Finally, the main limitation of this study is related to the sample size, since it was difficult to find companies willing to collaborate with this kind of research.